Investigating the Rhetoric of a President: a Rhetorical Discourse Analysis - Kabirun, Sharifa Sittie Zehanie Jali (JOALL (Journal of Applied Linguistics and Literature), 2024)
People engage in various types of discourse every single day. With everyone’s differences in attitudes, beliefs, and behaviours, persuasion is a skill that comes into play. Therefore, it is essential to develop an ability to analyze persuasive messages encountered critically (Borchers, 2005) and, hence, master the art of persuasion. This study, which delves into the rhetoric of former Philippine President Rodrigo Roa Duterte (PRRD), has yielded significant findings. Several speeches of PRRD have been scrutinized numerous times through Discourse Analysis (DA). Many researchers have employed Critical Discourse Analysis (CDA), while only a few have attempted to employ Rhetorical Discourse Analysis (RDA). Hence, the researcher conducted this study to enrich the literature on RDA further in PRRD’s speeches. In this study, the researcher conducted an RDA on the speech of PRRD entitled “Nation Address of President Rodrigo Roa Duterte on Coronavirus Disease 2019 (COVID-19) Pandemic” to identify and investigate the rhetorical devices and rhetorical elements found in the text which significantly played in generalizing the type of rhetoric the former President Duterte is. As revealed, PRRD used rhetorical devices such as description, personal pronouns, modals, cause-effect relationships, repetition, and evidence and authorities. Moreover, he also employed the three rhetorical elements such as logos through a cause-effect relationship, ethos through his Filipino citizenship, local or ethnic origin, and experiences being the president, and pathos through the display of varied emotions such as fear, sympathy and empathy, love and affection, respect, trust and assurance, and pity. In conclusion, PRRD is presented as a rhetor who utilizes the appeal of fear to exemplify his arguments, which are evident in the rhetorical devices and rhetorical elements in his speech.